PENGARUH KOMPETENSI SUMBER DAYA MANUSIA, SISTEM INFORMASI AKUNTANSI, DAN PENGENDALIAN INTERNAL TERHADAP KUALITAS LAPORAN KEUANGAN PADA CV INAURA ANUGERAH - Ibna Ridwanika Zahar; Badrus Zaman; Andy Kurniawan (Jurnal Ilmiah Akuntansi, 2025)
The study examined the impact of human resource competency, accounting information systems, and internal control on the quality of financial reports at CV Inaura Anugerah. To achieve this objective, the study employed a quantitative method with multiple linear regression analysis. A total of 54 participants participated in the study and were selected using a purposive sampling method. The study's findings indicate that, separately, human resource competency does not significantly influence the quality of financial reports. Conversely, SIA and internal control were shown to have a significant influence. Overall, all three aspects significantly impact the quality of financial reports. The uniqueness of the study is that the quality of financial reports is more influenced by the optimal performance of SIA and internal control implemented, compared to human resource competency. These findings lead the company to seek ways to improve the quality of the financial reports it produces